Gender gap–Gender-specific development in the field of obstetrics and gynecology in Germany in the last 20 years - Hertling, Stefan; Kaiser, Mario; Schleußner, Ekkehard; Loos, Franziska Maria; Eckhardt, Niklas; Graul, Isabel (Frontiers in Medicine, 2023)
Background Gender Gap refers to differences between men and women in terms of access to medical education, career development, and leadership positions in medical practice and research. Although women now make up most medical school graduates in many countries, they are often underrepresented in higher positions. Objective The aim of this study is therefore to analyze the gender-specific development in the field of Obstetrics and Gynecology in Germany over the past 20 years and to survey the current status quo. Materials and methods An narrative review was carried out on the development of female graduates of human medicine, the proportion of women in contract medical care and clinical care, as well as the gender-specific evaluation of obtaining a gynecological/obstetric additional qualification. habilitation figures in the field of Obstetrics and Gynecology were evaluated about gender distribution. All data were received from federal institutes. Results A total of 46.7% (n = 95,234) of all inpatient doctors were female. A total of 46.7% (n = 95,234) of the physicians in hospitals were female. A total of 46% (1,832/3,958) were the portion of females as assistant physicians, 39.8% (n = 45.551) as specialists, 35.3% (n = 18789) as senior physicians, 25.1% (n = 2394) as first senior physicians and 25% (n = 10) as chief physicians in hospital. A total of 64.6% (n = 3958) of the physicians in Obstetrics and Gynecology were female. A total of 46% (1,832/3,958) were the portion of females as assistant physicians, 64.6% (n = 3958) as specialists, 65.0% (n = 1919) as senior physicians, 26.4% (n = 207) first senior physicians and 25% (n = 10) as chief physicians in Obstetrics and Gynecology. Discussion The problem with the gender gap in medicine, does not seem to be access to teaching or starting a residency. But in the functions with increasing responsibility and management functions, e.g., as senior physicians, women are already rarely seen. In Obstetrics and Gynecology, too, there is a shortage of women in leading positions, despite the relatively high numbers, for example as senior physicians. Factors like maternity and establishing a family are points mentioned therefore, but also stereotypes seem to be considerable facts. Conclusion However, it is important to recognize the need for more women in higher positions in medicine and actively work to encourage more women to choose a career in medicine.